2017
DOI: 10.4103/ajns.ajns_351_16
|View full text |Cite
|
Sign up to set email alerts
|

A method for reconstruction of severely damaged spinal cord using autologous hematopoietic stem cells and platelet-rich protein as a biological scaffold

Abstract: Introduction:There have been attempts to alter the prognosis of severe spinal cord injury in different centers, but none of which have reliably altered the outcome. Some trials use stem cells (SCs) that produced widely differing results. We hereby add our experience in our center of a surgical reconstruction of the damaged spinal cord using a mixture of SCs and Platelet-Rich Protein (PRP) with fibrin coated as a biological scaffold.Materials and Methods:Four cases of severely damaged spinal cord have been oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In a retrospective investigation, Al-Zoubi et al [36] implanted purified autologous leukapheresis-derived CD34+ and CD133+ stem cells into 19 patients with chronic full SCI; over half of the patients showed segmental sensory or motor improvement after long-term follow-up. Ammar et al [37] revealed in a pilot trial, using a biological scaffold containing autologous HSCs and platelet-rich protein for four individuals with SCI, a patient who demonstrated motor and objective sensory improvement. Some prior research found a slight neurological improvement from transplanting neural stem/progenitor cells into people with chronic SCI.…”
Section: Advances and Prospects Of Stem Cell Therapy For Scimentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective investigation, Al-Zoubi et al [36] implanted purified autologous leukapheresis-derived CD34+ and CD133+ stem cells into 19 patients with chronic full SCI; over half of the patients showed segmental sensory or motor improvement after long-term follow-up. Ammar et al [37] revealed in a pilot trial, using a biological scaffold containing autologous HSCs and platelet-rich protein for four individuals with SCI, a patient who demonstrated motor and objective sensory improvement. Some prior research found a slight neurological improvement from transplanting neural stem/progenitor cells into people with chronic SCI.…”
Section: Advances and Prospects Of Stem Cell Therapy For Scimentioning
confidence: 99%
“…The implementation of blinding techniques is crucial to ensure the reliability of clinical trial outcomes. Many prior studies have failed to report adverse events comprehensively, potentially resulting in an overstatement of stem cell safety and efficacy [21,36,37]. Consequently, extending the follow-up period is essential to comprehensively investigate the safety profile of stem cell therapy.…”
Section: Drawbacks Of Stem Cell Therapy For Scimentioning
confidence: 99%
“…Recent studies indicated that SCs loaded with biological scaffolds could increase the survival rate of SCs, promote differentiation into neurons, increase the growth factor release, and improve axonal and myelin sheath regeneration [ 176 ]. Numerous studies indicated that SCI mice receiving biological scaffolds combined with SC transplantation demonstrated a better outcome on motor function than those that received SCs alone [ 177 179 ]. A growing number of studies indicated that 3D print might be another promising and exciting technology with huge potential for SCI treatment.…”
Section: Sc and Novel Approaches: Biomaterials 3d Print And Optomentioning
confidence: 99%
“…Anatomically, the IVD comprises a central highly hydrated nucleus pulposus (NP), a peripheral thin layer of the annulus fibrosus (AF), and upper and lower cartilage endplates (CEPs) [ 5 ]. Histologically, the NP mainly comprises water and a low density of notochord and NP cells and the extracellular matrix (ECM).…”
Section: Ivd and Iddmentioning
confidence: 99%